Sinergitas Mahasiswa Calon Guru Pendidikan Agama Islam Dalam Mengatasi Permasalahan Peserta Didik Bersama Guru Bimbingan Dan Konseling - Ummah Karimah; Sofiyan Ari Saputra; Ahmad Wafi; Heru Nugroho; Rafa Farhani; Siti Yulia Dewi Kartika (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine the perspective of students as prospective teachers in the field of Islamic Religius Education in solving student problems together with counseling teachers or school counselors. In this study, the authors used a qualitative approach, through direct data collection techniques through obeservations during Islamic guidance and counseling lectures and interviews with students. The research subject were Islamic Religious Education Students, Muhammadiyah University, Jakarta, South Tangerang City. The data collection technique used is interviews. The validity of data using triangulation. The data analysis techniques was carried out by going through the stages of data reduction, data presentation, and withdrawal. Based on the results of the study, it can be seen that students as prospective teachers in the field of Islamic Religious Education have a perspective on how to overcome student problems together with guidance and counseling teachers or school counselor after attending Islamic guidance and counseling courses that teachers in the field of Religious Education help in various programs Guidance and Counseling service have duties and roles in helping students overcome problems such as: violation